Assessment of some biochemical parameters of apple juices from two cashew varieties as affected by three regions of co´te d Ivoire (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
Some biochemical parameters of juices from two red and yellow cashew apple varieties from three regions of Cote d Ivoire were analyzed. The parameters such as proteins, total soluble solids, total sugars, dry matters, and ashes had contents in juices ranging from 0.35 ± 0.01 % to 0.65 ± 0.02 %, 9.66 ± 0.28 % to 14.40 ± 0.10 %, 270.20 ± 5.15 g/L to 381.04 ± 9.86 g/L, 8.94 ± 0.02 % to 11.45 ± 0.43 % and 1.19 ± 0.01 % to 1.51 ± 0.03 % respectively. Besides, the Analysis of Variance (ANOVA) indicated that the region and variety had significant effects (Pâ‰¤ 0.05) on these parameters. It so appeared significant differences (Pâ‰¤ 0.05) between their contents. As for pH, these values varying from 4.00 ± 0.10 to 4.74 ± 0.10, differed meaningfully (Pâ‰¤ 0.05) from one variety to another, whatever the region is. Otherwise, the results revealed that both red and yellow cashew apple varieties juices contained high rate of Tannins (1081.99 ± 34.64 - 2561.61 ± 95.11 mg/L), Flavonoids (223.83 ± 2.94 mg/L - 490.04 ± 5.32 mg/L) and total phenolic compounds (1587.59 ± 76.99 - 3043.03 ± 69.87 mg/L) whereas the carotenoid (0.97± 0.02 mg/mL -2.94 ± 0.02 mg/L) and Anthocyanin (6.57 ± 0.17 mg/L to 10.38 ± 0.15 mg/L) contents were found low. They also indicated yellow cashew apple variety juice didn't contain Anthocyanin content. Besides, the Analysis of Variance (ANOVA) showed that the region and variety main effect had significant effects (P 0.05) on these parameters. Thus, there were significant differences (P 0.05) between their rates. Furthermore, studies mineral elements (K, P, Mg, and Na) were only affected by improvement zone except to Na and they varied significantly (p 0.05). Red and yellow Cashew apple juices were the best sources of mineral elements and could be used in the diets of infants and young children. It was also rich in Vitamin C (210.61±5.01 mg/100mL and 403.73 ± 8.88 mg/100mL) and should be considered a potential supply source of adequate daily nutritional requirement for children and adults.